Immunotherapy combined with rh-endostatin improved clinical outcomes over immunotherapy plus chemotherapy for second-line treatment of advanced NSCLC - Huang, Hongxiang; Zhong, Peiyuan; Zhu, Xie; Fu, Silv; Li, Siling; Peng, Sujuan; Liu, Yangyang; Lu, Zhihui; Chen, Li (Frontiers in Oncology, 2023)
Background: Despite the fact that numerous clinical and preclinical studies have demonstrated the synergistic effects of combining antiangiogenic or chemotherapy with immunotherapy, no data have been found to indicate that combination therapy is more effective and safer as second-line therapy. Methods: We retrospectively compared the effectiveness and safety of ICIs plus rh-endostatin to ICIs plus chemotherapy in patients with advanced non-small cell lung cancer (NSCLC). The evaluation indicators of this study were progression-free survival (PFS), safety profile, objective response rate (ORR), disease control rate (DCR), and 1-year overall survival (OS). Results: The median PFS with immunotherapy plus rh-endostatin (IE) was 7.10 months (95% CI, 4.64 to 9.56) versus 5.13 months (95% CI, 4.29 to 5.97) with immunotherapy plus chemotherapy (IC) (HR, 0.56; 95%CI, 0.33 to 0.95). Treatment-related adverse events of grade 3 or 4 occurred in 7.5% of the IE group versus 25.0% of the IC group. The ORR in the IE group was 35.0% versus 20.8% in the IC group (P = 0.137), and the DCR in the IE group was 92.5% versus 77.1% in the IC group (P = 0.049). The 1-year OS rate for the IE group was 69.4%, which was higher than the 61.4% of the IC group. Conclusion: Our study demonstrates that ICIs in conjunction with endostatin therapy, demonstrate high efficacy and safety, suggesting that such a combination of therapy may be a viable treatment option for pretreated NSCLC patients in the future.